Odpowiedzi

2010-02-24T16:55:25+01:00
A) (2a+3b+4c+5d)+(3a+2b-c-4d) = 2a+3b+4c+5d + 3a+2b-c-4d = 5a+5b+3c+d
b) (3a+5b+c-4d)+(4a+6b-4c+d) (chyba zabrakło b, więc dopisałam)= 3a+5b+c-4d + 4a+6b-4c+d = 7a+11b-3c-3d
c) (a+b+3c+4d)+(-2a-2b-3c-4d) = a+b+3c+4d-2a-2b-3c-4d = -a-b
d) (a+b-3c-7d)+(a-2b-2c+d) = a+b-3c-7d+a-2b-2c+d = 2a-b-5c-6d
2010-02-24T16:56:57+01:00
A)
(2a+3b+4c+5d)+(3a+2b-c-4d) =
2a+3b+4c+5d+3a+3b-c-4d =
5a+6b+3c+d

b)
(3a+5b+c-4d)+(4a+6b-4c+d) =
3a+5b+c-4d+4a+6b-4c+d =
7a+11b-3c-3d

c)
(a+b+3c+4d)+(-2a-2b-3c-4d) =
a+b+3c+4d-2a-2b-3c-4d =
-a-b

d)
(a+b-3c-7d)+(a-2b-2c+d) =
a+b-3c-7d+a-2b-2c+d =
2a-b-5c-6d